Effects of supplementation with foliages of selected multipurpose trees, their mixtures or wheat bran on feed intake, plasma enzyme activities, live weight and scrotal circumference gains in Menz sheep - Melaku, S.; Peters, Kurt J.; Tegegne, Azage (Elsevier, 2004)
The experiment was conducted at Debre Zeit Research Station of the International Livestock Research Institute in Ethiopia for 126 days. Fifty-four male Menz sheep with initial live weight (LW) of 15.7+/-0.32 kg (mean+/-S.D.) were blocked on initial LW and randomly assigned to one of the nine treatments, giving six animals per treatment. The basal feed used in the experiment was tef (Eragrostis tef) straw. The supplement treatments consisted of wheat bran (positive control) or dried foliage of the multipurpose trees (MPT), Sesbania sesban 1198, S. sesban 15019, Acacia angustissima 15132, and Leucaena pallida 14203, or the mixtures of S. sesban 1198 and S. sesban 15019 with either L. pallida 14203 or A. angustissima 15132 at a ratio of 2:1. The level of supplementation was at 0.9% of LW on dry matter (DM) basis. The objectives of the experiment were to evaluate the effects of supplementation on feed intake, plasma activities of certain enzymes, daily LW and scrotal circumference gains. The crude protein (CP) content in the MPT leaves and their mixtures ranged between 21.6% and 27.8% of DM. Supplementation with mixtures of MPTs promoted higher organic matter (OM) (PPPPP>0.05) between treatments at the beginning and at the end of the experiment. It is concluded that supplementation with mixtures of MPTs promoted better utilization of nutrients and animal performance compared to sole MPTs or wheat bran in sheep fed on a basal diet of tef straw.